Possible role of tocopherols in the modulation of host microRNA with potential antiviral activity in patients with hepatitis B virus-related persistent infection: a systematic review. Issue 11 (17th October 2014) - Fiorino, S.; Bacchi-Reggiani, L.; Sabbatani, S.; Grizzi, F.; di Tommaso, L.; Masetti, M.; Fornelli, A.; Bondi, A.; de Biase, D.; Visani, M.; Cuppini, A.; Jovine, E.; et al.
Abstract : Hepatitis B virus (HBV) infection represents a serious global health problem and persistent HBV infection is associated with an increased risk of cirrhosis, hepatocellular carcinoma and liver failure. Recently, the study of the role of microRNA (miRNA) in the pathogenesis of HBV has gained considerable interest as well as new treatments against this pathogen have been approved. A few studies have investigated the antiviral activity of vitamin E (VE) in chronic HBV carriers. Herein, we review the possible role of tocopherols in the modulation of host miRNA with potential anti-HBV activity. A systematic research of the scientific literature was performed by searching the MEDLINE, Cochrane Library and EMBASE databases. The keywords used were 'HBV therapy', 'HBV treatment', 'VE antiviral effects', 'tocopherol antiviral activity', 'miRNA antiviral activity' and 'VE microRNA'. Reports describing the role of miRNA in the regulation of HBV life cycle, in vitro and in vivo available studies reporting the effects of VE on miRNA expression profiles and epigenetic networks, and clinical trials reporting the use of VE in patients with HBV-related chronic hepatitis were identified and examined. Based on the clinical results obtained in VE-treated chronic HBV carriers, we provide a reliable hypothesis for the possible role of this vitamin in the modulation of host miRNA profiles perturbed by this viral pathogen and in the regulation of some cellular miRNA with a suggested potential anti-HBV activity. This approach may contribute to the improvement of our understanding of pathogenetic mechanisms involved in HBV infection and increase the possibility of its management and treatment.